Portrait of Graduate Theology In Indonesia: The Conflict Between God's Needs and Self-Life Needs - GP, Harianto; Ming, David; Slamet Triadi; Novita Loma Sahertian (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
The background study explores Portrait of Graduate Theology in Indonesia as it relates to the dilemma between serving God and your own needs, particularly in light of the increasing number of theology graduates and their employment challenges. The increase in the number of theology majors by 13% raises concerns, given that 42% of these graduates face unemployment. This situation highlights a significant gap in theological education, where the quality may not meet the job market demands. The objective research aims to understand how theological education can better prepare students for spiritual service and practical life needs. This research employs a literature review approach, examining existing theoretical frameworks and empirical data on the social dynamics surrounding theology graduates. It examines various customs, norms, and societal expectations influencing these graduates' educational experiences and career paths. The increasing number of theology graduates juxtaposed with high unemployment presents a critical challenge for theological education. By adopting holistic approaches integrating spiritual formation with practical applications, institutions can better prepare students to navigate their dual roles in serving God and fulfilling personal life needs. This alignment could ultimately reduce unemployment rates among theology graduates while enriching their contributions to society.